The role of marriage in immigrants' human capital investment under liquidity constraints - Sarit Cohen-Goldner; Chemi Gotlibovski; Nava Kahana (Institute for the Study of Labor (IZA), 2006)
This paper presents a two-period human capital investment model of married and single immigrants under binding liquidity constraints, which explains alternative patterns in the host country's labor market. These patterns are also compared to those of natives who face a perfect capital market. By extending Eckstein and Weiss' model (2004) from the case of single immigrants with accessibility to a perfect capital market to the case of credit-constrained immigrant families, it is shown that the comparative advantage in investment that determines which spouse will invest more in local skills depends on his/her imported human capital growth rate rather than on its level. This comparative advantage can lead to full or partial specialization in work and investment activities within immigrant households. However, the level invested by each spouse is non-increasing with the level of the imported human capital of the spouse with the comparative advantage in investment, whereas it is non-decreasing with the level of imported human capital of the other spouse. A comparison of pre and post marriage investment indicates that the spouse with the comparative advantage in investment will increase his/her investment in human capital after his/her marriage, whereas the other spouse will decrease it. The more efficient investment due to marriage enables the achievement of a Pareto improvement.
Keywords: 330; Ehe; Migranten; Investition; Humankapital; Verschuldungsrestriktion; Theorie